Diseño y construcción de un banco didáctico de refrigeración por agua helada para el laboratorio de fluidos del AEIRNNR. - Gálvez Tapia, Wilson Eduardo (2013)
Our thesis is focused on the design and construction of a system of using cooling water Frost, through a minichiller of 1 ton of capacity for the laboratory of fluids of the AEIRNNR, with the purpose that the fellow students who are studying our career, can internship in the corresponding to the refrigeration and air conditioning by using this type of system with practical guides and easy understanding. The team has closed two subsystems: the first inside the cooling components and expansion of the air conditioning and the second serves to cool the refrigerant through the double tube with cross flow of water condenser. The first subsystem has the following: A compressor, double tube condenser, evaporator coil that cools the water at room temperature up to 7° C that are stored in the tank of the evaporator and pump for water re-circulation is carried to a Fan-Coil dispelling the air conditioning in the space to be air conditioned, to then return water back to the evaporator tank and repeat the same cycle. All components mentioned above are controlled through a Thaler of control that owns the team. The second subsystem is the double tube condenser, a re-circulation pump that sucks the water from a tank recirculator and passes it through the double tube condenser to be subsequently forwarded to the tank of water circulation cooling to temperature and atmospheric pressure.